State, Nationalism, and Civic Exclusion: Historical Notes from the Bolivian Case - Gomes, David (Cuadernos de Historia Moderna, 2012)
The shortcomings of nation-building in Bolivia have traditionally been explained as the failure of the integration project designed by nineteenth-century republicanism. This article argues that, on the contrary, liberal consolidation of the nation and the adoption of expanded citizenship would have harmed the interests of Creole political and economic elites. The conservation of its class power inherited from the colonial hierarchy oriented, at first, the extension of the colonial pact with indigenous people and, later on, the change of the economic model, the privatization of communal lands and the racialization of the indigenous issue. Altiplano communities, caracterized by a weak sense of national belonging, reacted to these attacks on their autonomy with tactics of submission, negotiation and violence, while taking advantage of conflicts between factions of the Creole elite to become an influential player in Bolivian political life.